Open text editing tools for open scholarly communications - Wilm, Johannes (Septentrio Conference Series, 2017)
Scholarly communication is undergoing a revolution with the move to open access. This has opened new opportunities and also new challenges. One of the most problematic issues are the costs of publishing. Some of this may be excessive profits of some publishers, but another part are actual costs associated with typesetting and document conversion. In 2012, the open source Fidus Writer editor was born with the vision of creating a fully web-based semantic editor for academics that would not require manual typesetting after the authors are finished with their text. Since 2015 the GESIS – Leibniz Institute for the Social Sciences and University of Bonn have been working on the “Open Scholarly Communications in the Social Sciences” project. The project is financed by the German Research Foundation, DFG, and it has been enhancing Fidus Writer and connecting it with a number of other tools, such as citation databases for automatic citation retrieval and the Open Journals Systems (OJS) to offer an integrated peer-review process. The aim is to create a fully integrated system for social Scientists and others that does away with conversion steps and makes scientific text creation both less costly and improves the tools available, also for non-technically inclined users. While several other projects have come into being simultaneously with Fidus Writer, their focus has been somewhat different: ShareLatex/Overleaf have focused on LaTeX users and is therefore not suitable for scientists who do not code. Other editors are either not open source, not working as collaborative editors or do not provide the tools needed by humanists and social scientists. We have written several papers collaboratively using our combined tool that have been submitted and published and are now working with two journals to obtain real-world experience using Fidus Writer with social scientists in the journal peer review process. In this poster I would like to present the current status of our tool and project.